THE IMPACT OF INTEGRATED MARKETING COMMUNICATION ON CONSUMER PURCHASE DECISION AT HAWAI WATERPARK MALANG - Virtuecrat, Laksamana (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
This study aimed to determine the effect of Advertising (X1), Sales Promotion (X2), Interactive Marketing (X3), and Event Marketing (X4) on purchasing decision (Y) at Hawai Waterpark Malang. A total of 215 respondents were selected on this study using purposive sampling techniques and methods of non- probability sampling by filling out a questionnaire that has been through the test validity and reliability to obtain data. Data were analyzed using multiple linear regressions. The analysis showed that, variable Advertising (X1), Sales Promotion (X2), Interactive Marketing (X3), and Event Marketing (X4) have significant influence partially on purchasing the entrance/admission ticket to Hawai Waterpark Malang, with Fcount 38.477 and significance 0,000. The results of this analysis suggest that, variable Advertising (X1) dominant influence by 43% in influencing purchasing decisions. Value Adj. R2 obtain the results for 0.412, which means the variable advertising (X1), sales promotion (X2), Interactive Marketing (X3), and event marketing (X4) is able to influence consumer purchase decisions to enter Hawai Waterpark at 42.3% and the remaining 57.7% is explained by other factors not discussed in this study. Keywords: Advertising, Sales Promotion, Interactive Marketing, Event Marketing, and Purchasing Decision.